Pengaruh Kualitas Harga Layanan dan Kepuasan terhadap Kesetiaan Usia Millenial Berkunjung ke Tempat Wisata - Alvianna, Stella; Hidayatullah, Syarif (Sekolah Tinggi Pariwisata AMPTA, 2020)
This study focuses on analyzing the effects of product quality, price and quality of information on customers loyalty with customers satisfaction as a mediator variable toward the tourist destinations of Wendit Tourism Park. All tourism Diploma Program students aged 15-34 years were the population in this study which 75 respondents were taken as a sample. The results revealed the quality of the product had no effect directly the sattisfaction of the customerrs of Wendit tourism, while the price affected directly the satisfaction of the customers of Wendit tourism, the quality of service directly affected the satisfaction of the customers of Wendit tourism, the quality of the product dirrectly affected the loyalty of Wendit tourism customers, the price had no effect Wendit tourism customer loyalty directly, the quality of service had no effect the loyalty of Wendit tourism customers directly and product quality indirectly affected the loyalty of Wendit tourism customers through customer satisfaction.